Behind the Curtain: What Makes the Land of OB GYN Appealing to Our Students. (October 2017) - Green, Isabel; Riddle, Julia
Abstract : BACKGROUND: In 2005, in response to a decline in residency applications in OBGYN, the American College of Obstetrics and Gynecology Presidential Task Force outlined strategies for attracting medical students to OBGYN. Our program implemented interventions across all years of medical school education, increased efforts to "teach the teachers, " and improve faculty and resident relations with students. Application rates increased, but little is still known about which interventions work. METHODS: This qualitative study received IRB approval. Students applying or recently matched into OB GYN residency programs from the Class of 2014–2016 were included. Eleven participants completed a phone interview exploring why they chose OB GYN, focusing on positive and negatives experiences. The survey instrument was designed to include open ended questions and a Likert-type survey. Grounded theory methodology was used for analysis. Participants received a 50 Starbucks card. RESULTS: Preliminary analysis identified the following themes: 1) potential for a "meaningful" job and a future role in women's health, advocacy for women or empowerment of women; 2) first impressions in the clinical clerkship and "welcoming" teams; 3) content and diversity of our field; 4) impact of supportive mentors in career decisions. DISCUSSION: Participants identify important events that even precede medical school, but commonly highlight finding meaning in their work, and identifying with others that share in their interest and goals as guiding them toward OB GYN.